SARS-CoV-2 IgG spike protein antibody response in mRNA-1273 Moderna® vaccinated patients on maintenance immunoapheresis – a cohort study - Gaggl, Martina; Aschauer, Constantin; Aigner, Christof; Bond, Gregor; Vychytil, Andreas; Strassl, Robert; Wagner, Ludwig; Sunder-Plassmann, Gere; Schmidt, Alice (Frontiers in Immunology, 2022)
Background: The SARS-CoV-2 pandemic increased mortality and morbidity among immunocompromised populations. Vaccination is the most important preventive measure, however, its effectiveness among patients depending on maintenance immunoglobulin G (IgG) apheresis to control autoimmune disease activity is unknown. We aimed to examine the humoral immune response after mRNA-1273 Moderna® vaccination in immunoapheresis patients. Methods: We prospectively monitored SARS-CoV-2 IgG spike (S) protein antibody levels before and after each IgG (exposure) or lipid (LDL) apheresis (controls) over 12 weeks and once after 24 weeks. Primary outcome was the difference of change of SARS-CoV-2 IgG S antibody levels from vaccination until week 12, secondary outcome was the difference of change of SARS-CoV-2 IgG S antibody levels by apheresis treatments across groups. Results: We included 6 IgG and 18 LDL apheresis patients. After 12 weeks the median SARS-CoV-2 IgG S level was 115 (IQR: 0.74, 258) in the IgG and 1216 (IQR: 788, 2178) in the LDL group (p=0.03). Median SARS-CoV-2 IgG S reduction by apheresis was 76.4 vs. 23.7 % in the IgG and LDL group (p=0.04). The average post- vs. pre-treatment SARS-CoV-2 IgG S rebound in the IgG group vs. the LDL group was 46.1 and 6.44 %/week from week 8 until 12. Conclusions: IgG apheresis patients had lower SARS-CoV-2 IgG S levels compared to LDL apheresis patients, but recovered appropriately between treatment sessions. We believe that IgG apheresis itself probably has less effect on maintaining the immune response compared to concomitant immunosuppressive drugs. Immunization is recommended independent of apheresis treatment.